2014 3rd International Conference on User Science and Engineering (I-USEr) 2014
DOI: 10.1109/iuser.2014.7002701
|View full text |Cite
|
Sign up to set email alerts
|

Web readability for students with Dyslexia: Malaysian case study

Abstract: Dyslexia is a specific reading disability in word recognition, spelling and decoding. Students with Dyslexia require special adjustments to the text and text environment to be able to read better. Current studies have shown that many assistive technologies such as software application and other tools are available in aiding Dyslexia's student in reading. However, websites that support Dyslexia's student in reading are very minimal. This discourages Dyslexia's student to use the Internet. Therefore there is a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The works of [54,55] raise the problem of proposing an ontology to facilitate the development of e-learning tools aligned with the needs of dyslexic students, but no practical supporting solutions are introduced. In the works of [56,57], instead, the readability of websites for dyslexic people is analyzed and improved, but this can be considered only as a first step toward their full inclusion in the learning system. A second step is performed in [58], where web applications are also taken into account, but only the preliminary phase of a dyslexia-friendly collaborative learning system is presented.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The works of [54,55] raise the problem of proposing an ontology to facilitate the development of e-learning tools aligned with the needs of dyslexic students, but no practical supporting solutions are introduced. In the works of [56,57], instead, the readability of websites for dyslexic people is analyzed and improved, but this can be considered only as a first step toward their full inclusion in the learning system. A second step is performed in [58], where web applications are also taken into account, but only the preliminary phase of a dyslexia-friendly collaborative learning system is presented.…”
Section: Related Workmentioning
confidence: 99%
“…This fact highlights the necessity to combine both supporting methodologies in order to be capable of helping dyslexic students during their academic career. Conversely, the vast majority of approaches proposed until now [56][57][58][59][60][61][62][63][64][65] have only taken into account digital tools, neglecting to also create, in parallel, a list of the best practices to be followed to provide support to dyslexic students. The supporting strategies that obtained the highest scores are taking pauses during lessons, hosting lessons online, repeating the studied material and making the program and the slides of the course available, which are considered useful by about 96 to 99% of the participants in the questionnaire.…”
Section: Supporting Toolmentioning
confidence: 99%
“…Certain language processing areas of the brain are affected, making it difficult to acquire reading, spelling, or writing skills [10]. Students with dyslexia need special adjustments to the text and text environment to read better [11,12]. Dyslexia has some warning signs included recognizing letters, letter inversion, missing words, letter confusion, difficulty in understanding sounds and letters, delay in remembering numbers or letters, difficulty in following instructions and learning routines, and difficulty in creating words with sounds and slow reading or easy to forget the words they have learned [13].…”
Section: Definitionmentioning
confidence: 99%
“…Sarpudin and Zambri showed that students with dyslexia could read better and more easily through information and communication technology [11]. It has become a new way of teaching and learning for special needs, which can help people with dyslexia improve teaching and learning efficiency.…”
Section: Visual and Auditory Stimulation Of The Flipped Classroommentioning
confidence: 99%
“…Most of the Malaysian-based research Define Dyscalculia as the inability to acquire arithmetic skills and comprehend the concept of numbers (Miyundy et al, 2019;Mazeyanti et al, 2018;Sarpudin & Zambri, 2014;Zulkifli et al, 2012). (Wei et al, 2019) defined Dyscalculia as the arithmetic difficulties, computing capacity significantly lower than its intelligence, age and education level.…”
Section: Definitionmentioning
confidence: 99%